The Treatise of the Vessels (Massekhet Kelim) and traditions concerning Eden and the gold of Parvaim - Akagi, Kai 1987- (2020)
The Treatise of the Vessels identifies the gold of the Temple as gold of Parvaim from Eden. The idea that the Temple's gold came from Eden is otherwise unattested, but it may have come from exegetical reflection on scriptural texts and traditions concerning gold and Eden. (1) The description of gold as "good" is unique to Gen 2 and 2 Chr 3. (2) A chain of scriptural texts could associate the gold of the Temple with Eden through linking Parvaim, Ophir, and Havilah. (3) Traditions concerning golden fruit could have contributed to associating the gold of the Temple with fruit trees in Eden. These intertexts and traditions not only provide examples of the kind of scriptural exegesis that may have been formative in the composition of the Treatise of the Vessels but also demonstrate similarity to more widely attested traditions concerning the gold of Parvaim, the Garden of Eden, and the Temple in the Midrash, Talmud, and Targum Pseudo-Jonathan. Recognizing such similarities may be an initial step in further consideration of the context of the text's composition.
Keywords: Eden; Treatise of the Vessels; Gold; scriptural exegesis; Massekhet Kelim; Parvaim